Board Structure and Firm Performance in Shariah Compliant Listed Firms; Does Muslim Member Play Important Role on Firm Performance? - Siti Fasihah, Mohd Sunif; Mohd Waliuddin, Bin Mohd Razali; Sharifah Sabrina, Syed Ali (2015)
The main objective of this study is to examine the relationship board structure and firm performance in Shariah Compliant firms. Sample consists of 169 Malaysian Shariah-compliant listed firms is obtained from the Bursa Malaysia for period of 2011 to 2013. The multiple regression analysis is used to estimate the relationship between board structure and firm. After controlling leverage, the results show that there is a significant positive relationship between board size and firm performance by means to strengthen the link between corporations and their environments. The result also finds a significant negative relationship between Muslim member and firm performance. It is opined that tend to avoid opportunistic behaviours such as earning management because it is forbidden by Islamic law. And as for the rest of findings, there is no significant relationship among other variables and the firm performance.